Does gender matter? A moderation analysis of renewable energy and sustainability performance in Indonesian higher education institutions - Dwi Sulistiani; Yona Octiani Lestari; Yuanda Kusuma (Education and Development Research, 2026)
This study aims to provide empirical evidence on the influence of renewable energy (RE) on sustainability performance (SP), while also examining the role of gender in this relationship. A quantitative research method employing a survey technique was used with university lecturers in Indonesia as respondents. 232 samples were measured using random sampling which was processed using the SmartPLS 4.0 application. The results found a significant influence of renewable energy on sustainability performance. However, gender was not found to moderate the effect of renewable energy on sustainability performance. This study confirms that the success of renewable energy strategies in improving sustainability performance in universities depends not only on technology and investment, but also on gender diversity. In the context of sustainability research, gender socialization theory provides a robust theoretical foundation to support the argument that gender equality is a vital prerequisite for achieving equitable, inclusive, and sustainable development for all. Thus, this study makes a significant contribution to the literature on renewable energy, sustainability, and gender, offering new insights into the development of more inclusive and sustainable higher education policies. The results also confirm the relevance of public policies that link the sustainability agenda to gender equality in the higher education sector.